The Development of Stowage Planning Model for General Cargo Ship and Cargo Barge Vessel - Rebecca Rouli Samaria; Armand Omar Moeis; Timothy Thamrin Andrew H. Sihombing; Arry Rahmawan Destyanto (Jurnal Penelitian Transportasi Laut, 2021)
As a maritime country whose water area is three times wider than its land, Indonesia has one of the ways to increase the logistic activities especially in adjusting to the development of the industry 4.0 by enhancing the productivity of maritime logistics in a way of streamlining the action at unit terminal containers. Stevedoring is a one of very important logistics activities in port operational ecosystem. In order to optimize the performance of the port, the efficiency of the stowage planning process is done. Some factors which can be evolved in stowage planning are processing time, ship stability, and minimum over stow. This research uses the stowage planning algorithm to develop an application in Python programming language. This application will eventually be used to create a stowage plan map for general cargo ship and cargo barge vessel in by prioritizing the ship stability, as well avoiding low over stow in a short time. With Python programming language a routine operational four hours job that used Microsoft Excel, only requires far less time with 10-15 seconds.